Digital Control, Symbolic Power, and the Shift of Violence: Non-Physical Violence in Urban Parent–Child Relationships in Bengkulu City - An Nisaa Wulansari; Ledyawati Ledyawati; Ayu Wijayanti (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
Violence against children in family settings is increasingly shifting from visible physical forms to more subtle non-physical and digitally mediated practices. Emotional neglect, verbal intimidation, and parental digital control are frequently normalized as discipline, despite their significant psychological consequences for children. This study examines the forms of non-physical and digital violence in parent–child relationships, analyzes the social factors driving this shift in violence patterns, and explores how symbolic meanings constructed through daily interactions shape differing perceptions of violence. Using a qualitative case study design grounded in the social definition paradigm and symbolic interactionism, this research was conducted in an urban residential area of Bengkulu City. Data were collected through participant observation, semi-structured interviews with 14 informants (parents and children aged 10–15), and documentation. The findings reveal that emotional, verbal, and digital violence dominate parent–child interactions, particularly through excessive monitoring, verbal threats, and unilateral restrictions on digital access. Parents interpret these practices as protective discipline, while children experience them as intimidation and distrust. Parental anxiety over digital risks, social pressure, and limited digital parenting literacy further contribute to the normalization of such practices. The study contributes to family sociology by conceptualizing digital control as a form of symbolic power, where authority is exercised not through physical force but through control over digital access and communication. It extends symbolic interactionism by demonstrating how digital infrastructure devices, messaging platforms, and internet access mediates the production and normalization of non-physical violence in everyday family interactions. These findings highlight the need to reconsider child protection and digital parenting frameworks to account for subtle forms of symbolic and relational violence within families.